2005
DOI: 10.1254/jphs.fpe04008x
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of Phospholipase D Expression and Activation in Ventricular Pressure-Overload Hypertrophy

Abstract: Abstract. Evidence for a role of phospholipase D (PLD) in cellular proliferation and differentiation is accumulating. We studied PLD activity and expression in normal and hypertrophic rat and human hearts. In rat heart, abdominal aortic banding (constriction to 50% of original lumen) caused hypertrophy in the left ventricle (as shown by weight index and ANP expression) by about 15% after 30 days without histological evidence of fibrosis or signs of decompensation and in the right ventricle after 100 days. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…To add even more complexity, earlier studies report that the PLD product phosphatidic acid activates PDE4D3 (Grange et al, 2000) and that PLD expression is upregulated in response to ventricular pressureoverload hypertrophy (Peivandi et al, 2005). These findings implicate that alterations in activity and/or expression of factors that are part of cAMP-sensing multiprotein complexes, such as PDE4D3 (DodgeKafka et al, 2005), or factors that determine the subcellular localization of Epac, such as phosphatidic acid (Consonni et al, 2012), exhibit different signaling properties and therefore alter the ability of Epac to act either anti-and/or pro-hypertrophic in the heart.…”
Section: Biology Of the Epac Signalosomementioning
confidence: 99%
“…To add even more complexity, earlier studies report that the PLD product phosphatidic acid activates PDE4D3 (Grange et al, 2000) and that PLD expression is upregulated in response to ventricular pressureoverload hypertrophy (Peivandi et al, 2005). These findings implicate that alterations in activity and/or expression of factors that are part of cAMP-sensing multiprotein complexes, such as PDE4D3 (DodgeKafka et al, 2005), or factors that determine the subcellular localization of Epac, such as phosphatidic acid (Consonni et al, 2012), exhibit different signaling properties and therefore alter the ability of Epac to act either anti-and/or pro-hypertrophic in the heart.…”
Section: Biology Of the Epac Signalosomementioning
confidence: 99%
“…Recent studies showed that statin therapy affects caveolar turnover by limiting their endocytosis [128]. Atorvastatin has also been shown to modulate the cholesterol enrichment of the lipid rafts [129].…”
Section: Pathophysiological Implicationsmentioning
confidence: 99%
“…Fas receptor activation is an important component in hypertrophy induced by pressure-and volume-overload and recently it has been reported that Fas-mediated hypertrophy is dependent upon the IP 3 pathway, which is functionally interconnected to the phosphoinositide-3 kinase/AKT/glycogen synthase kinase-3β pathway; both pathways act in concert to cause nuclear factor of activated T cells nuclear translocation and subsequent hypertrophy [130]. Recent evidence suggests that ventricular pressure overload hypertrophy led to an upregulation of PLD isozymes both in rat and human heart, which may be due to potentiation of PLD activation by α-adrenoceptor and PKC stimulation [131]. PA produced by the activation of PLD also stimulates SL PLC activity [56,132].…”
Section: Role Of Phospholipases In Cardiac Hypertrophy and Heart Failurementioning
confidence: 99%